STUDENTS' PERCEPTIONS OF USING READTHEORY.ORG IN READING COMPREHENSION - Krisna Ismawati; Syafryadin Syafryadin (Universitas Galuh, 2022)
The purpose of this study was to determine and explore students' perceptions of the use of ReadTheory in reading comprehension. Quantitative descriptive was used to conduct this research. The researcher used a closed questionnaire using five Likert scales to collect data. In this study 50 students as the sample.Based on the overall results, the researcher can conclude that the students' perception of the use of ReadTheory in reading comprehension of the majority of the subjects showed positive responses, especially on the points related to the use of the platform towards changes in their abilities for the better even though the changes were not too significant. This can be seen from their responses that they will continue to use ReadTheory in the future because they feel that they have received many benefits. Therefore, the researcher can conclude that students' perception of using the ReadTheory platform in reading comprehension tends to be positive because it provides benefits and changes their ability to understand reading texts.